Spanish seamen: clothing (circular) - Tewson, Vincent
025a-0087-001 Telegraphic Address: TRADUNIC, SOWEST, LONDON. Telephone: VICTORIA 9020. Trades Union Congress Department: International Our Ref. HVT/AC/305 Your Ref. General Secretary SIR WALTER CITRINE, KBE TO WHOM ALL COMMUNICATIONS SHOULD BE ADDRESSED. TRANSPORT HOUSE, SMITH SQUARE, LONDON, S.W.1. 20th July, 1939. SPANISH SEAMEN: CLOTHING. In the case of two Trades Councils, the question has been raised as to the method which should be adopted in regard to providing clothing for the Spanish seamen. It has been intimated to us that local appeals could meet the situation, but the Trades Councils desired to know whether we were anticipating any expenditure on outfitting the men when emigration can be effected. In this connection, I should be most grateful if everything possible could be done in your locality to meet the requirements of the men in the way of clothing. The position is still not clear in regard to emigration, and even when it does come about, it will be a very expensive matter. We shall only be able to assist with the cost of the fares according to the funds available. Any money spent on clothing would only mean a reduction in the amount available for fares. I thought I would mention this matter, as no doubt some question will have arisen in your mind on this point, and I trust that it will be possible for the clothing problem to be dealt with entirely in the locality. Yours sincerely, H. V. TEWSON Assistant Secretary. 292/946/25a/87